Penafsiran Ibnu Katsir terhadap Ayat-Ayat Isra’ Mikraj - Ahmad Asyraf bin Mohd Asri; Zainuddin Zainuddin (TAFSE: Journal of Qur'anic Studies, 2019)
Faith means belief in the heart, words in the mouth and practice with the limbs. Every believer must believe in Allah, His angels, His books, His Messengers, the Last Day, and belief in both good and bad destiny. Believing in the miracles of the apostles includes believing in the apostles. Among the miracles of the Prophet SAW is the Isra 'Mikraj event. This event is clearly mentioned in QS. al-Isrā' (17): 1 and QS. al-Najm (53): 5-18. This incident is also found in the hadiths of various narrations. The commentators have described in depth this great event, among them is Ibn Kathir. In the theory of creed, the arguments and proofs related to the issue of faith must be with definite arguments (qath'i), and cannot use conjectures (dzan). However, Ibn Kathir uses the dha'īf hadith and the āhād hadith in his interpretation of Isra' Mikraj. The research method used by the author is library research, including secondary data collection and processing of the data that has been obtained using descriptive-analytical methods. The author collects data according to the findings, then analyzes the data and understands Ibn Kathir's thoughts on the verses related to Isra and Mikraj. Iman berarti keyakinan dalam hati, perkataan di lisan dan amalan dengan anggota badan. Setiap mukmin wajib beriman kepada Allah Swt, malaikat-malaikat-Nya, kitab-kitab-Nya, Rasul-Rasul-Nya, hari akhir, dan beriman kepada takdir baik maupun yang buruk. Mempercayai mukjizat-mukjizat para rasul termasuk beriman kepada rasul. Di antara mukjizat Nabi Saw adalah peristiwa Isra’ Mikraj. Peristiwa tersebut disebut secara jelas dalam QS. al-Isrā’ (17): 1 dan QS. al-Najm (53): 5-18. Peristiwa ini juga terdapat dalam hadis dari pelbagai riwayat. Para mufasir telah menguraikan dengan mendalam peristiwa besar ini, di antaranya adalah Ibnu Katsir. Dalam teori akidah, dalil dan hujjah yang berkaitan dengan masalah akidah haruslah dengan dalil yang pasti (qath‘i), tidak bisa menggunakan dugaan (dzan). Namun, Ibnu Katsir menggunakan hadis dha‘īf dan hadis āhād dalam penafsirannya tentang Isra’ Mikraj. Metode penelitian yang digunakan penulis adalah library research (penelitian kepustakaan), meliputi pengumpulan data sekunder dan mengolah data-data yang telah didapatkan dengan menggunakan metode deskriptif-analitis. Penulis menghimpun data sesuai hasil temuan, lalu melakukan analisis data tersebut dan memahami pemikiran Ibnu Katsir terhadap ayat-ayat yang berkaitan dengan Isra’ dan Mikraj.